A little help from my friends: caring for premature babies in a war zone - Harris Heather (BMC, 2007)
Abstract This paper is a narrative of some aspects of my work as a midwife with Médecins Sans Frontieres (MSF) in West Africa. I was situated in an isolated north-western regional hospital in an area under rebel military control in 2004-2005 in the Côte d'Ivoire during the civil war which divides the north and south of the country. Access to health care is severely curtailed in this politically unstable environment resulting in much avoidable illness including many premature births. It is a short account of methods used to care for premature babies in a resource poor setting. Equipment was basic, necessitating a creative use of available resources. Providing warmth, oxygen and adequate feeding were often sufficient for a successful outcome for many premature babies. This paper is a combination of descriptions of health care interspersed with case studies.